PERAN SERTA MASYARAKAT DALAM PENGADAAN SARANA AIR BERSIH DI DESA LASARA IDANOI KECAMATAN GIDO KABUPATEN NIAS - Rahmi Fitri Laoli; evi Naria; Irnawati Marsaulina (Lingkungan dan Kesehatan Kerja, 2013)
The community in the provision of clean water in the village of Lasara Idanoi Gido district of Nias Regency.Water is the very important component for human life. Clean water should come from clean water supply and safe. Absence of a water supply led to a lack of clean water needs resulting in the emergence of health complaints.This study is a descriptive survey method. The population as much as 206 heads of households with 67 samples. Samples were taken by using a systematic random sampling technique. The purpose of this study was to determine the community in the provision of clean water supply in the village of Lasara Idanoi Gido district of Nias Regency. The result of the research, the level of respondents knowledge about clean water and clean water supply category as moderate (55%), respondents attitudes towards water use and clean water supply category as good (94%). Respondents strongly agreed the implementation of water supply procurement activities by mutual assistance (89,5%). Role models as well as hand-picked by the respondents is PNPM Independent Rural (88%). Resources of the community respondents classified as good (93%). Enviromental resources that can be utilized as a source of clean water is rain water because rainfall in this area is quite high. Therefore, it is expected the participation of the community and village in cooperation with the organizers PNPM Independent Rural so that provision of clean water supply in the village of Lasara Idanoi can be realized. Keywords : Public Participation, Clean Water Supply